ANALISIS GERAKKAN FOREHAND DALAM PERMAINAN TENIS LAPANGAN - Helprida Sinambela; Lylian female; Alnathan Naibaho; Stipen Harianja; Henike Lusiana sembai; Nurkadri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to provide an in-depth analysis of the forehand movement in tennis as one of the fundamental techniques that significantly contributes to athlete performance. The forehand was selected because it is the most frequently used stroke in both offensive and defensive situations, making an understanding of its movement patterns, biomechanical principles, and technical factors essential for improving playing quality. The analysis was conducted by observing each phase of the movement, including the preparation phase, backswing, forward swing, ball contact, and follow-through. Each phase was examined based on variables such as balance, motor coordination, body rotation, energy transfer, racket positioning, and the dominant muscle activity involved. The findings indicate that the effectiveness of the forehand stroke is strongly influenced by foot stability, synchronized hip and shoulder rotation, and the athlete’s ability to utilize body momentum efficiently. Proper execution enables optimal energy transfer from the lower limbs to the torso, arm, and racket, thereby increasing ball speed without sacrificing accuracy. Additionally, precise timing at ball contact and appropriate racket angles play a crucial role in determining the ball’s direction, height, and spin. Athletes who can maintain consistent movement coordination tend to produce more powerful, stable, and controlled strokes with fewer errors. This study emphasizes that mastering the forehand technique is not solely dependent on physical strength but also on the athlete’s ability to coordinate the entire body, understand movement rhythm, and apply biomechanical principles effectively. These findings provide practical implications for coaches and athletes in designing more targeted training programs that focus on strengthening core muscles, improving balance, enhancing flexibility, and refining movement synchronization. Therefore, this analysis is expected to serve as a reference for future research and as a foundation for developing training methods to improve the quality and consistency of the forehand stroke in tennis.